The complete idiot's guide to Facebook - Belicove, Mikal E 1965-; Kraynak, Joe (New York Alpha, 2012)
From start to success, this user-friendly guide walks you through Facebook's dizzying array of options and helps you set up an account you'll enjoy using
Mastering Facebook basics -- Getting more involved with Facebook -- Harnessing the power of Facebook apps -- Utilizing Facebook for businesses and organizations
Includes index
1 13
Keywords: Facebook (Electronic resource); Online social networks; Social networks -- Computer network resources; Web sites -- Design